High-precision semiconductor wavelength sensor based on a double-layer photo diode - Amthor, Thomas; Hofmann, Christoph S.; Knorz, Jürgen; Weidemüller, Matthias (Review of scientific instruments, 2011)
We present a wavelength sensor setup for monochromatic visible light, based on the double-layer photo diode WS-7.56. Employing high-precision electronics and automatic compensation of different error sources, we achieve a measurement accuracy of ±0.025 nm with a resolution below 0.01 nm. The described apparatus is particularly suited for the determination of small laser frequency deviations in atomic physics experiments. Various design issues as well as error sources and diode characteristics are discussed.
Gesehen am 02.03.2022